Profile of benign breast diseases in Kashmiri women: a prospective study - Wani, Mumtazdin; Mir, Shabir Ahmad; Dar, Mohammad Hanief (International Surgery Journal, 2017)
Background: Though benign breast diseases are very common, not many studies have focussed on this entity. In Kashmir valley, no major study has been undertaken before, to look into the profile of the benign breast diseases in women. Methods: This prospective study was conducted in the Postgraduate Department of General Surgery of SMHS Hospital from October 2012 to September 2014. The patients with features of benign breast diseases were subjected to detailed history, clinical examination and investigations. Analysis was done using this data. Results: 80% of the benign breast lesions presented in the second and third decades of life. Mean age was 24.46 years. Most common benign breast lesion was fibroadenoma. Lump in the breast was the predominant symptom. Duration of symptoms mostly ranged from 1 to 6 months. There was a slight preponderance of lesions in the right breast. Most of lesions presented in upper outer quadrant. 81.39% of the patients had only a solitary lump.76.74% of lumps had a size of 2 to 5cm. Clinicopathological correlation in case of fibroadenoma, showed 60% sensitivity, 75% specificity, PPV=85.71% and NPV=42.85%. Cytohistological correlation in case of fibroadenoma, showed 85% sensitivity, 87.5% specificity, PPV=94.4% and NPV=70%. 38 cases (38%) were managed conservatively and 62 cases (62%) were managed surgically. Conclusions: Results grossly similar to other parts of the word were obtained. Fibroadenoma was the most common benign lesion encountered followed by fibroadenosis and breast abscess. Majority of breast lumps were painless. Conservative approach for fibroadenoma is acceptable option in the adolescents.